Astrocytic Changes in Mitochondrial Oxidative Phosphorylation Protein Levels in Parkinson's Disease. Issue 2 (15th November 2021) - Chen, Chun; Mossman, Emily; Malko, Philippa; McDonald, David; Blain, Alasdair P.; Bone, Laura; Erskine, Daniel; Filby, Andrew; Vincent, Amy E.; Hudson, Gavin; Reeve, Amy K.
Abstract: Background: Mitochondrial dysfunction within neurons, particularly those of the substantia nigra, has been well characterized in Parkinson's disease and is considered to be related to the pathogenesis of this disorder. Dysfunction within this important organelle has been suggested to impair neuronal communication and survival; however, the reliance of astrocytes on mitochondria and the impact of their dysfunction on this essential cell type are less well characterized. Objective: This study aimed to uncover whether astrocytes harbor oxidative phosphorylation (OXPHOS) deficiencies in Parkinson's disease and whether these deficiencies are more likely to occur in astrocytes closely associated with neurons or those more distant from them. Methods: Postmortem human brain sections from patients with Parkinson's disease were subjected to imaging mass cytometry for individual astrocyte analysis of key OXPHOS proteins across all five complexes. Results: We show the variability in the astrocytic expression of mitochondrial proteins between individuals. In addition, we found that there is evidence of deficiencies in respiratory chain subunit expression within these important glia and changes, particularly in mitochondrial mass, associated with Parkinson's disease and that are not simply a consequence of advancing age. Conclusion: Our data show that astrocytes, like neurons, are susceptible to mitochondrial defects and that these could have an impact on their reactivity and ability to support neurons in Parkinson's disease. Abstract : The use of imaging mass cytometry to interrogate alterations in OXPHOS protein expression in astrocytes within the substantia nigra. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society.